La actividad física y deportiva de las PVVIH :Del interés por la práctica al acceso a la práctica (Revisión de la bibliografía) - Sylvain Ferez; Athanasios Pappous; Sébastien Ruffié (FEADEF, 2010)
The scientific literature about AIDS and physical exercise has been traditionally dominated by biomedical approaches. The first studies which were published in the beginning of the nineties focused mainly on the transmission risks of the virus during sports. Later studies were concerned with the physiological logics of the exercise on HIV-positive persons. Since the end of the nineties the therapeutic progress contributed to envisage sport as a way to mediate the side effects of medical treatments. However the present review highlights a serious gap in the literature on Sport and HIV using a sociological point of view. The authors of this article argue that the time has come to consider sociological data linked to the experiences of HIV/AIDS in order to understand the difficulties and barriers that seropositive persons have to face when participating in sport.